Whose Story? Competing versions of English in a London school - Yandell, John; Hardcastle, John (L1-Educational Studies in Language and Literature, 2024)
In this article, we look closely at two accounts of parallel lessons in the same London school. Early on in our pre-service teacher education programme, student teachers are asked to write about a lesson they have observed. Soumeya and Faduma each described a lesson where the novel, In the sea there are crocodiles by Fabio Geda, was being read. The observations are of parallel lessons taught by two different teachers. We use these accounts to explore differences in pedagogy and in the versions of English that are instantiated in the lessons. These forms of practice bear family resemblances to many other lessons—and have complex histories. Our interest lies in the ways in which they reflect or contest the view of the subject that dominates the landscape of policy in England today